(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2020)
Background: The purpose of the current study is to describe clinical manifestations, management and its outcome of patients who were diagnosed as glaucomatocyclitic crisis at the Glaucoma Department Chittagong Eye Infirmary and Training Complex (CEITC) Chattogram and Eye Department, Chittagong Medical College. Materials and methods: It is a hospital based observational case series study. Study period was from 1st July 2010-to 30th June 2012.Unilateral ocular hypertension cases of unexplained origin referred to glaucoma clinic from outpatient department of CEITC and Eye Department, Chittagong Medical College Hospital (CMCH) were included in this study. Detail history taking and ocular examinations were done that included stitlamp biomicroscopy, applanation tonometry, gonioscopy, fundoscopy and visual field analysis. Glaucomatocyclitic Crisis (GCC) was diagnosed according to mentioned criteria. Management detail was recorded. Patients were followed up after one weak, 1 month, 3 months of initial visit. Examination and investigation findings were documented as much as possible. Sample size was 45. Results: A total numbers of 45 patients with GCC were included. For the better understanding the results, the total patients (N=45) were categorized into 2 age groups that are 20-49 and 50+. Percentage of patients into these groups are 51.1% (n=23) and 48.9% (n=22) respectively. In total 45 patients, 37 were male and 8 were female. 53.3% patients (n=24) presented with decreased visions, 15.6% patients (n=7) with both pain and occasional redness, 13.3% patients (n=6) with mild discomfort, 11.1% patients (n=5) with recurrent redness, 8.9% patients (n=4) with occasional halos, 4.4% patients (n=2) with occasional eye ache and 2.2% patient (n=1) with loss of vision. Mean IOP of affected eyes was 30mm hg before treatment and 15mm hg after treatment. Angles were open in all cases. At presentation 81.2% patients (n-37) presented with glaucomatous optic disc C:D ratio (0.8-1):1. 77.77% patients(n=35) needed flurometholone, 4.44% cases (n=2) needed dexamethasone and 4.44% patients (n=2) needed prednisolone acetate topical eye drop to control inflammation. 13.33% patients (n=6) were not treated with any steroid as they resolved spontaneously. 91% patients needed anti glaucoma medications 9% needed filtration surgery with Ologen implantation to control IOP. Conclusion: Early diagnosis with meticulous examinations and investigations are needed to manage a GCC case. As it is an elusive disease, proper explanation of the disorder to the patient to get good compliance from them is necessary to achieve good medical treatment outcome. Good filtration surgery with Ologen implantation is still successful to control IOP. But regular careful monitoring to the patient is mandatory to perfectly manage and prevent the irreversible visual consequences of recurrence of the disease. JCMCTA 2020 ; 31 (1) : 81-85